The Cloisters : [large type] a novel - Hays, Katy, 1982- (Blackstone Publishing, 2022)
Ann Stilwell, working as a curatorial associate at New York City's gothic museum, finds hidden medieval tarot cards and gets caught up in a game of power, seduction, and ambition that turns deadly.